Synthesis method of carbon-based sheet-shaped magnetic nanoparticle aggregate
Graphene is prepared by chemical vapor deposition and mixed with modified magnetic iron oxide nanoparticles to adjust the mixing time and particle size to prepare two-dimensional flexible magnetic aggregates with excellent magnetic responsiveness and biocompatible, which solves the problems of poor dispersion, unstable magnetic strength and sensitivity to environmental factors in the prior art.
Patent Information
- Application Number
- CN202411831024.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-04-22
AI Technical Summary
The existing magnetic nanoparticle synthesis methods have problems such as poor dispersion, unstable magnetic strength and sensitivity to environmental factors.
Graphene was prepared by chemical vapor deposition, and magnetic iron oxide nanoparticles with different morphology were prepared by synthesis of iron oleate precursors and thermal decomposition. Then, surface modification was performed using sodium citrate, and the modified magnetic iron oxide nanoparticles were mixed with graphene, and the mixing time and particle size were adjusted to prepare two-dimensional flexible magnetic aggregates.
Two-dimensional flexible magnetic aggregates with excellent magnetic responsiveness and biocompatible were prepared, which solved the problems of poor dispersion, unstable magnetic strength and sensitivity to environmental factors, and achieved the synthesis of high-performance, monodispersed flexible magnetic nanoparticle aggregates.
Smart Images

Figure CN119858912A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nano materials, and in particular relates to a method for synthesizing carbon-based flaky magnetic nanoparticle aggregates. Background Art
[0002] With the rapid development of biomedicine, rapid and efficient detection of pathogens has become a research hotspot. Rapid and portable pathogen detection devices can avoid the risk of disease, reduce the number of deaths, and reduce economic losses. At present, the main methods for detecting pathogens are plate culture counting method, polymerase chain reaction method and enzyme-linked immunosorbent assay. The plate culture counting method has high accuracy, but this method generally takes more than 12 hours and requires enrichment. The polymerase chain reaction method is sensitive and has high accuracy, but it requires professional technicians to operate, and it is difficult to achieve instant and rapid detection. The enzyme-linked immunosorbent assay can achieve rapid detection, but the antibodies are difficult to preserve and are expensive. Traditional biological detection methods have defects such as complex operation and low sensitivity. With the rapid development of molecular biology technology, polymerase chain reaction (PCR), DNA hybridization and loop-mediated isothermal amplification (LAMP), biochips and other methods have also been used to detect foodborne pathogens, and have achieved good accuracy and sensitivity, but there are also many problems in practical applications: high false positive rate, expensive instruments, high detection cost, complex detection steps, long detection time, etc.
[0003] Magnetic nanoparticles have shown great application potential in the fields of biological detection, targeted drug delivery and cell separation due to their superior biocompatibility, large specific surface area and sensitive magnetic responsiveness. Compared with traditional biological detection methods, magnetic nanoparticles provide faster, more sensitive and more specific detection methods. They provide new possibilities for solving the technical problems of poor dispersibility, unstable magnetic strength and sensitivity to environmental factors in existing synthesis methods. Summary of the invention
[0004] The purpose of the present invention is to provide a method for synthesizing carbon-based flaky magnetic nanoparticle aggregates to solve the technical problems of poor dispersibility, unstable magnetic strength and sensitivity to environmental factors in existing synthesis methods.
[0005] To achieve the above object, the present invention adopts the following technical solution:
[0006] A method for synthesizing carbon-based flaky magnetic nanoparticle aggregates comprises: preparing graphene by chemical vapor deposition and transferring it to a target substrate; synthesizing an iron oleate precursor and preparing magnetic iron oxide nanoparticles with different morphologies; surface modifying the magnetic iron oxide nanoparticles by sodium citrate; mixing the modified magnetic iron oxide nanoparticles with graphene, and adjusting the mixing time and particle size to obtain a two-dimensional flexible magnetic aggregate.
[0007] A carbon-based flaky magnetic nanoparticle aggregate synthesis system comprises: a preparation transfer module for preparing graphene by chemical vapor deposition and transferring it to a target substrate; a synthesis preparation module for synthesizing an iron oleate precursor and preparing magnetic iron oxide nanoparticles of different morphologies; a modification module for performing surface modification on the magnetic iron oxide nanoparticles by using sodium citrate; and a mixing preparation module for mixing the modified magnetic iron oxide nanoparticles with graphene and adjusting the mixing time and particle size to obtain a two-dimensional flexible magnetic aggregate.
[0008] A computer-readable storage medium stores a computer program, wherein the computer program is configured to execute the above-mentioned method for synthesizing carbon-based flaky magnetic nanoparticle aggregates when running.
[0009] An electronic device comprises a memory and a processor, wherein the memory stores a computer program, and the processor is configured to execute the method for synthesizing carbon-based flaky magnetic nanoparticle aggregates through the computer program.
[0010] In the present invention, graphene is prepared by chemical vapor deposition and transferred to a target substrate; an iron oleate precursor is synthesized and magnetic iron oxide nanoparticles of different morphologies are prepared; sodium citrate is used to modify the surface of the magnetic iron oxide nanoparticles; the modified magnetic iron oxide nanoparticles are mixed with graphene, and the mixing time and particle size are adjusted to obtain a two-dimensional flexible magnetic aggregate, thereby preparing a two-dimensional flexible magnetic aggregate with excellent magnetic responsiveness and biocompatibility, solving the technical problems of poor dispersibility, unstable magnetic strength and sensitivity to environmental factors in the existing synthesis method, and achieving the technical effect of synthesizing a new type of high-performance, monodisperse flexible magnetic nanoparticle aggregate. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 It is a schematic diagram of a process for synthesizing a carbon-based flaky magnetic nanoparticle aggregate in an embodiment of the present invention;
[0012] Figure 2 This is a schematic diagram of the CVD chemical vapor deposition method in an embodiment of the present invention;
[0013] Figure 3 This is a schematic diagram of the process of transferring graphene using the PMMA method in an embodiment of the present invention;
[0014] Figure 4 Schematic diagram of spherical magnetic nanoparticles in an embodiment of the present invention;
[0015] Figure 5 Schematic diagram of cubic nanoparticles in an embodiment of the present invention;
[0016] Figure 6 Schematic diagram of synthesizing two-dimensional sheet-like magnetic nanoparticle aggregates in an embodiment of the present invention;
[0017] Figure 7 It is a structural schematic diagram of a carbon-based flaky magnetic nanoparticle aggregate synthesis system in an embodiment of the present invention. DETAILED DESCRIPTION
[0018] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. The advantages and features of the present invention will become more apparent from the following description and claims. It should be noted that the drawings are all in very simplified form and are not in precise proportions, and are only used to conveniently and clearly assist in explaining the purpose of the embodiments of the present invention.
[0019] It should be noted that, in order to clearly explain the content of the present invention, the present invention specifically cites multiple embodiments to further illustrate different implementations of the present invention, wherein the multiple embodiments are enumerated rather than exhaustive. In addition, for the sake of brevity of explanation, the contents mentioned in the previous embodiments are often omitted in the subsequent embodiments. Therefore, the contents not mentioned in the subsequent embodiments can refer to the previous embodiments accordingly.
[0020] Example 1
[0021] A method for synthesizing carbon-based flaky magnetic nanoparticle aggregates, such as Figure 1 As shown, the method includes:
[0022] S102, preparing graphene by chemical vapor deposition and transferring it to a target substrate;
[0023] S104, synthesizing iron oleate precursor and preparing magnetic iron oxide nanoparticles with different morphologies;
[0024] S106, surface modification of magnetic iron oxide nanoparticles using sodium citrate;
[0025] S108, mixing the modified magnetic iron oxide nanoparticles with graphene, and adjusting the mixing time and particle size to obtain a two-dimensional flexible magnetic aggregate.
[0026] As an optional implementation, graphene is prepared by chemical vapor deposition, including: using copper foil as a substrate, and adjusting the growth rate by controlling the gas flow rate under the conditions of 1000° C. and 0.5 atm to prepare graphene.
[0027] As an optional implementation manner, transferring to the target substrate includes: transferring to the target substrate with the assistance of PMMA.
[0028] As an optional embodiment, the PMMA-assisted transfer to the target substrate includes: spin coating PMMA on the sample surface, and transferring the graphene to the target substrate by etching copper foil.
[0029] The graphene is not limited to being prepared by chemical vapor deposition (CVD) technology and transferred to a target substrate with the assistance of PMMA, and the target substrate is not limited to being a silicon substrate (SiO2 / Si).
[0030] As an optional implementation, synthesizing an iron oleate precursor includes: dissolving ferric chloride and sodium oleate to prepare the iron oleate precursor.
[0031] As an optional implementation manner, the preparation of magnetic iron oxide nanoparticles with different morphologies includes: preparing magnetic iron oxide nanoparticles with different morphologies in oleylamine and octadecene by thermal decomposition.
[0032] Specifically, it is not limited to dissolving FeCl3 and sodium oleate to prepare an iron oleate precursor, and preparing magnetic iron oxide nanoparticles by thermal decomposition in oleylamine and octadecene.
[0033] As an optional embodiment, the surface of the magnetic iron oxide nanoparticles is modified by using sodium citrate, including: the surface of the magnetic iron oxide nanoparticles is modified by a blending reaction of sodium citrate in an aqueous phase.
[0034] Specifically, the surface modification of the magnetic iron oxide nanoparticles is achieved by a mixing reaction of sodium citrate in an aqueous phase.
[0035] As an optional embodiment, adjusting the mixing time and particle size includes adjusting the loading amount and relative spacing of magnetic iron oxide particles on the graphene surface to control the magnetic strength of the magnetic aggregate.
[0036] The preparation of two-dimensional flexible magnetic aggregates also includes adjusting the loading amount of magnetic iron oxide particles on the graphene surface and their relative spacing to control the magnetic strength of the magnetic aggregates.
[0037] As an optional embodiment, after obtaining the two-dimensional flexible magnetic aggregates, the method further includes: evaluating the dispersibility and stability of the flexible magnetic aggregates in physiological saline by particle surface charge analysis and hydration radius characterization.
[0038] After the two-dimensional flexible magnetic aggregates are prepared, the dispersibility and stability of the flexible magnetic aggregates in physiological saline are evaluated by particle surface charge analysis and hydration radius characterization. The aggregates have excellent magnetic responsiveness and biocompatibility and are suitable for biological detection and targeted capture of microbial pathogens.
[0039] Specifically, the specific implementation of the above-mentioned carbon-based flaky magnetic nanoparticle aggregate synthesis method is not limited to including the following key steps:
[0040] 1. Preparation of carbon-based sheet nanomaterials
[0041] (1) Preparation of graphene
[0042] Graphene is generated by CVD method. A flat substrate (copper substrate) is used as a catalyst and substrate. A certain carrier gas (hydrogen H2) and a carbon source (ethylene gas C2H4 and methane gas CH4) are introduced under high temperature and low pressure environment and kept at 1000℃ for a period of time. Graphene products can be generated on the substrate surface. After the product is generated on the substrate, it needs to be transferred. The flow chart of CVD chemical vapor deposition method is not limited to the following. Figure 2 shown.
[0043] In the CVD process, in addition to the carbon source, a carrier gas is also needed to transport the carbon source gas to the reaction area and help control the reaction environment. The carrier gas can help adjust the pressure of the reaction atmosphere and in some cases can also act as a reducing agent to remove oxides on the copper surface.
[0044] (2) Transfer of graphene
[0045] The graphene generated by CVD is deposited on the surface of the copper foil to form a thin layer of two-dimensional material to obtain the Gr / Gu sample. Next, the graphene needs to be transferred. Spin-coating PMMA on the surface of the Gr / Gu sample is specifically not limited to:
[0046] ①Put Gr / Gu on the coating machine and drop a small amount of PMMA on the surface. Spin coating stage 1, low speed rotation 500rad / min, coating for 10 seconds; spin coating stage 2, high speed rotation 4000rad / min, coating for 60 seconds;
[0047] ②Take out the sample, place it on a heating table, heat and dry it at 80℃ for 3 minutes to obtain a PMMA / Gr / Gu sample;
[0048] ③Put PMMA / Gr / Gu flat in 1mol / L ammonium persulfate solution. The sample floats on the surface of the solution. The copper foil under the sample reacts with the solution and is etched. When the yellow copper foil is no longer visible to the naked eye, pick up the PMMA / Gr with a silicon wafer (SiO2 / Si), heat and dry it on a heating plate to obtain a PMMA / Gr / SiO2 / Si sample.
[0049] ④ Soak PMMA / Gr / SiO2 / Si in acetone solvent to dissolve and remove PMMA to obtain Gr / SiO2 / Si sample. The specific process of transferring graphene from copper foil to silicon substrate is not limited to the following: Figure 3As shown. Since large-area graphene itself cannot exist independently, in the process of graphene being separated from the copper foil and not combined with the silicon substrate, PMMA acts as a supporting layer for graphene, protecting the graphene and ensuring its integrity and structural stability for subsequent functionalization.
[0050] (3) Characterization of graphene probe
[0051] Raman spectroscopy is an efficient method for graphene detection. As the number of graphene layers gradually increases, the electronic structure of graphene gradually changes. Raman detection can effectively reflect the characteristics of the electronic structure changes of graphite and graphene. The number of graphene layers can be inferred by analyzing the characteristic peaks of the Raman spectrum. Specifically, the main peaks of graphite and graphene are ~1584cm -1 The G peak at 2700 cm -1 The 2D peak at G comes from E 2g The 2D peak represents the double electron double resonance mode of graphene. The third relatively weak characteristic peak is 1350cm -1 The defect peak (D peak) is around 2.3cm. This peak does not originate from the original graphene. When there is damage inside or at the edge of the sample in the system and the degree of defect is high, the D peak can be observed. As the number of graphene layers increases, the position and relative height of the G peak and 2D peak will change. In terms of the position of the G peak, the position of single-layer graphene is 3-5cm higher than that of bulk graphite. -1 . For single-layer graphene, the 2D peak is usually a sharp single peak, so the I2D / IG (ratio of the intensity of the 2D peak and the G peak) ratio of single-layer graphene is usually greater than 1; while in multi-layer graphene, the 2D peak becomes broader, and may split in the case of multiple layers. As the number of layers increases, the I2D / IG ratio gradually decreases until it approaches 0. Specifically, the 2D peak position of single-layer graphene is roughly the same as the lower peak position in the graphite 2D peak, and the 2D peak intensity of single-layer graphene is about four times that of the G peak. Within the range of few-layer graphene, the intensity of the G peak of graphene increases with the increase in the number of graphene layers, while the intensity of the 2D peak decreases relative to the G peak.
[0052] Detection by Raman spectroscopy:
[0053] ① Determine the number of layers: The number of graphene layers can be determined by detecting specific peak positions and intensity ratios. Single-layer graphene usually exhibits unique G peak and 2D peak characteristics in Raman spectroscopy. Among them, the shape and position of the 2D peak (especially in the case of a single layer, the 2D peak is a sharp single peak) is the key basis for distinguishing single-layer and multi-layer graphene. In addition, the I2D / IG ratio of single-layer graphene is usually greater than 1, while the I2D / IG ratio of multi-layer graphene will gradually decrease until it approaches 0;
[0054] ② Detect defects: Raman spectroscopy can also reveal whether the graphene sample has defects or doping. For example, the presence of the D peak indicates the presence of defects, and the ID / IG ratio (the intensity ratio of the D peak and the G peak) can quantify the degree of defects. High-quality graphene should have a lower ID / IG ratio;
[0055] ③ Check uniformity: By scanning multiple points for Raman testing, the uniformity of graphene in the entire sample area can be checked. This is especially important for subsequent applications, because uneven graphene may affect the performance of the final product.
[0056] 2. Synthesis of Magnetic Iron Oxide Particles
[0057] Since magnetic particles of different morphologies have different magnetic dipole moments and can generate different induced magnetic fields and magnetic field coupling strengths, magnetic particles of different morphologies are prepared to meet different needs, such as Figure 4 . Figure 5 shown.
[0058] (1) Preparation of iron oleate precursor
[0059] ①2mmol ferric chloride and 6mmol sodium oleate were dissolved in a mixed solution of 20mL anhydrous ethanol and 20mL deionized water. The solution was heated to 75℃ for 4h. After cooling to room temperature, 10mL benzyl ether was added to extract the dark red-brown ferric oleate into the organic layer, and then washed three times with deionized water. The final ferric oleate complex was stored in benzyl ether as a stock solution, and the concentration of iron ions in the stock solution was determined by inductively coupled plasma atomic emission spectroscopy (ICP-AES).
[0060] ②FeCl3·6H2O (2.7 g, 10 mmol) and sodium oleate (9.125 g, 30 mmol) were added to a 100 mL (4:3:7, v / v) mixed solution of ethanol, deionized water and n-hexane, and refluxed at 70°C for 4 h; the upper reddish-brown n-hexane solution containing oleic iron was separated and washed three times with deionized water (10 mL) and the n-hexane was evaporated to obtain a dark reddish-brown oily mixture containing oleic iron.
[0061] ③ Add the above-mentioned iron oleate mixture (9 g), octadecene (25 g) and a certain amount of oleic acid or sodium oleate into a three-necked flask. In a nitrogen atmosphere, heat the mixture to 320°C at a rate of 3-5°C / min, and heat with stirring at this temperature for 30 min, then cool to room temperature, ventilate, add isopropanol (50 mL) to precipitate magnetic Fe3O4 nanoparticles, centrifuge, wash 3 times with n-hexane and ethanol (1 / 5, v / v), and finally disperse in n-hexane or toluene for use.
[0062] (2) Preparation of spherical magnetic iron oxide single particles
[0063] ① Add 10 mmol of ferric chloride and 30 mmol of ferric oleate to a mixture of ethanol, deionized water and hexane and stir at room temperature for 4 hours. Then, reflux the mixture at 70°C for 4 hours, collect the upper reddish-brown component with a separatory funnel, and wash with deionized water to obtain the ferric oleate component.
[0064] ② Add oleylamine, ferric oleate and octadecene solution into a three-necked flask, stir and mix at room temperature under argon protection atmosphere. After 30 minutes, raise the temperature to 320℃ at 3-5℃ per minute and maintain for 30 minutes. Then cool the reaction system to room temperature, precipitate the black product with propanol, wash it three times with n-hexane and ethanol, and disperse it in n-hexane and toluene.
[0065] (3) Preparation of flake and rod-shaped magnetic iron oxide single particles
[0066] ① Sodium oleate (9.125 g, 30 mmol) and FeCl3·6H2O (2.7 g, 10 mmol) were added to 70 mL of methanol and kept at this temperature for 3 h. Then a yellow-brown solid was collected and washed with methanol to remove the NaCl crystals attached to it to obtain an iron oleate precursor. The method for preparing other iron precursors is similar to the above method, that is, sodium oleate is replaced by sodium stearate, sodium laurate and sodium acetate.
[0067] ② In a three-necked glass bottle, dissolve iron oleate (5mmol) in 25mL of octadecene, and then add sodium oleate (1.522g, 5mmol). Under nitrogen atmosphere, heat the entire system to 120℃ with a heating jacket at a heating rate of 3-5℃ / min. In order to remove low molecular weight substances in the system, keep this temperature for 0.5h. Then raise the system temperature to 210℃ at a heating rate of 1℃ / min, keep it at this temperature for 15h, and finally raise the temperature to 240℃ and keep it for 1h, then cool it to room temperature. Add 50mL of isopropanol and centrifuge at 8000r / min for 8min. Then neutralize the methanol with chloroform and wash it 3 times. Finally, spread the obtained iron oxide nanosheets in chloroform or n-hexane for storage.
[0068] ③ In a three-necked glass bottle, dissolve iron oleate (5 mmol) in 25 mL of octadecene, and then add oleic acid (2.5 mmol) and sodium methoxide (5 mmol). The other steps are the same as those in ①.
[0069] (4) Sodium citrate coated iron oxide nanomaterials
[0070] All iron oxide nanoparticles of all morphologies were modified with sodium citrate on the surface of iron oxide nanoparticles by ligand exchange. 10 mg of iron oxide nanomaterials were precipitated with ethanol and dispersed in 10 mL of tetrahydrofuran, to which 5 mL of aqueous solution of 20 mg of sodium citrate was added, and the solution was reacted for 4 h at room temperature under N2 protection. After the reaction was completed, the iron oxide nanoparticles adhered to the bottom of the reaction bottle or on the stirring bar, and were centrifuged and precipitated and dispersed in deionized water. The iron oxide nanoparticles in the aqueous phase were purified by a filter membrane (0.22 μm) for use and stored in a refrigerator at 4 °C.
[0071] 3. Preparation of two-dimensional flexible magnetic aggregates
[0072] Using graphene as a template and the functionalized molecules on the graphene surface as coordination centers, citric acid-modified iron oxide particles are mixed with graphene in an aqueous phase to prepare two-dimensional flexible iron oxide. By adjusting the mixing time, the loading amount of magnetic iron oxide particles on the graphene surface and the relative spacing of the magnetic beads are controlled. By adjusting the size of the added iron oxide magnetic beads, the magnetic properties of the lamellar magnetic bead aggregates are controlled. The stability of the flexible magnetic aggregates is evaluated by particle surface charge analysis, combined with hydration radius characterization and dispersibility in physiological saline. The synthesized two-dimensional flaky magnetic nanoparticle aggregates are not limited to Figure 6 shown.
[0073] Specifically, the specific implementation of the above-mentioned carbon-based flaky magnetic nanoparticle aggregate synthesis method is not limited to including the following steps:
[0074] Step 1: Material preparation and synthesis.
[0075] Select high-purity chemical reagents (99.999% H2, 99.9% C2H4 gas, 99.99% CH4 gas, etc.) as reaction precursors, use CVD to synthesize graphene, and determine reaction parameters (such as temperature, pressure, gas flow, etc.) to ensure that a uniform and high-quality graphene film is obtained. The specific operation is to adjust the growth rate of graphene by controlling the gas flow rate under low pressure conditions of 1000°C and 0.5atm, for example, the ratio of H2 to C2H4 and CH4 is 5:1 and 10:1 respectively.
[0076] Step 2: Cleaning and drying after graphene transfer.
[0077] For the transferred graphene, use an ultrasonic cleaner to place the transferred sample in a cleaning tank containing deionized water or ethanol, set the ultrasonic frequency to 40kHz, and clean for 5-10 minutes to remove any remaining copper salts and other impurities. After cleaning, blow dry the sample with nitrogen or dry it in an oven at 60°C for 30 minutes to ensure that there is no moisture or impurities on the sample surface.
[0078] Step three: characterization and screening of graphene.
[0079] Raman spectroscopy is used to analyze and compare the ID / IG ratios of different samples to ensure that the selected graphene samples have an appropriate number of layers and low defects. By detecting the characteristics of the G peak and 2D peak, single-layer or few-layer graphene samples with fewer defects are screened out to ensure the reliability and consistency of subsequent applications.
[0080] Step 4: Synthesis of magnetic iron oxide particles.
[0081] Magnetic iron oxide particles with different morphologies were prepared by preparing an iron oleate precursor and using a thermal decomposition method. First, FeCl3 and sodium oleate were dissolved in a mixed solution of ethanol and deionized water and heated to react to obtain an iron oleate precursor; then, in the presence of oleylamine and octadecene, spherical, flaky and rod-shaped magnetic iron oxide nanoparticles were synthesized by controlling the reaction temperature and time. Finally, the stability and biocompatibility of the particles were enhanced by sodium citrate modification, providing a basic material for the subsequent preparation of two-dimensional flexible magnetic aggregates.
[0082] Step 5: Preparation of two-dimensional flexible magnetic aggregates.
[0083] The citric acid-modified iron oxide particles were mixed with graphene in water; the mixing time was adjusted to control the loading amount of magnetic iron oxide particles on the graphene surface and the relative spacing between the magnetic beads; the size of the iron oxide magnetic beads was adjusted to control the magnetic strength. The dispersibility of the particles in physiological saline was evaluated by analyzing the surface charge and characterizing the hydration radius; the preparation conditions were optimized based on the evaluation results to ensure that the flexible magnetic aggregates had good stability.
[0084] In the present application embodiment, graphene is prepared by CVD method, and PMMA assisted transfer technology is utilized to transfer it to the target substrate. Subsequently, by synthesizing iron oleate precursor, and preparing magnetic iron oxide nanoparticles of different morphologies by thermal decomposition in oleylamine and octadecene. In order to enhance the stability and biocompatibility of the particles, sodium citrate is further used to surface modify the magnetic iron oxide nanoparticles. Finally, by co-mixing the modified magnetic iron oxide nanoparticles with graphene in an aqueous phase, adjusting the mixing time and particle size, a two-dimensional flexible magnetic aggregate with excellent magnetic responsiveness and biocompatibility is prepared, achieving a novel high-performance, monodisperse flexible magnetic nanoparticle aggregate synthesis, and providing an effective solution for the targeted capture of biological detection and microbial pathogens.
[0085] Example 2
[0086] A carbon-based sheet-like magnetic nanoparticle aggregate synthesis system, such as Figure 7 As shown, the system includes:
[0087] A preparation and transfer module 702, for preparing graphene by chemical vapor deposition and transferring it to a target substrate;
[0088] The synthesis preparation module 704 is used to synthesize an iron oleate precursor and prepare magnetic iron oxide nanoparticles with different morphologies;
[0089] A modification module 706 is used to modify the surface of the magnetic iron oxide nanoparticles using sodium citrate;
[0090] The mixing preparation module 708 is used to mix the modified magnetic iron oxide nanoparticles with graphene, and adjust the mixing time and particle size to obtain a two-dimensional flexible magnetic aggregate.
[0091] Optionally, the preparation transfer module 702 prepares graphene by chemical vapor deposition, including: using copper foil as a substrate, and adjusting the growth rate by controlling the gas flow rate under the conditions of 1000° C. and 0.5 atm to prepare graphene.
[0092] Optionally, the transfer of the preparation transfer module 702 to the target substrate includes: transferring to the target substrate with the assistance of PMMA.
[0093] Optionally, the preparation transfer module 702 transfers the graphene to the target substrate through PMMA assistance, including: spin coating PMMA on the sample surface, and transferring the graphene to the target substrate by etching copper foil.
[0094] Optionally, the synthesis preparation module 704 synthesizes the iron oleate precursor, including: dissolving ferric chloride and sodium oleate to prepare the iron oleate precursor.
[0095] Optionally, the synthesis preparation module 704 prepares magnetic iron oxide nanoparticles with different morphologies, including: preparing magnetic iron oxide nanoparticles with different morphologies by thermal decomposition in oleylamine and octadecene.
[0096] Optionally, the modification module 706 uses sodium citrate to perform surface modification on the magnetic iron oxide nanoparticles, including: performing a blending reaction of sodium citrate in an aqueous phase to achieve surface modification on the magnetic iron oxide nanoparticles.
[0097] Optionally, the mixing preparation module 708 adjusts the mixing time and particle size, including: adjusting the loading amount and relative spacing of the magnetic iron oxide particles on the graphene surface to control the magnetic strength of the magnetic aggregate.
[0098] Optionally, after the two-dimensional flexible magnetic aggregates are obtained by the mixing preparation module 708, the method further includes: evaluating the dispersibility and stability of the flexible magnetic aggregates in physiological saline by particle surface charge analysis and hydration radius characterization.
[0099] In an embodiment of the present application, graphene is prepared by chemical vapor deposition and transferred to a target substrate; an iron oleate precursor is synthesized, and magnetic iron oxide nanoparticles of different morphologies are prepared; the magnetic iron oxide nanoparticles are surface modified using sodium citrate; the modified magnetic iron oxide nanoparticles are mixed with graphene, and the mixing time and particle size are adjusted to obtain a two-dimensional flexible magnetic aggregate, thereby preparing a two-dimensional flexible magnetic aggregate with excellent magnetic responsiveness and biocompatibility, which solves the technical problems of poor dispersion, unstable magnetic strength and sensitivity to environmental factors in existing synthesis methods, and achieves the technical effect of synthesizing a new type of high-performance, monodisperse flexible magnetic nanoparticle aggregates.
[0100] Example 3
[0101] Another aspect of the embodiments of the present invention further provides an electronic device for implementing the above-mentioned method for synthesizing carbon-based flaky magnetic nanoparticle aggregates, and the electronic device is not limited to being a terminal device or a server in the system. The electronic device is not limited to including a memory and a processor, the memory stores a computer program, and the processor is configured to execute the steps in any of the above-mentioned method embodiments through the computer program.
[0102] Example 4
[0103] Another aspect of the embodiments of the present invention provides a computer program product or computer program, which includes computer instructions stored in a computer-readable storage medium. The processor of the computer device reads the computer instructions from the computer-readable storage medium, and the processor executes the computer instructions, so that the computer device executes the method provided in various optional embodiments of the above-mentioned carbon-based sheet-like magnetic nanoparticle aggregate synthesis method. Wherein, the computer program is configured to execute the steps of any of the above-mentioned method embodiments when running.
Claims
1. A method for synthesizing carbon-based flaky magnetic nanoparticle aggregates, characterized in that: include: Prepare graphene using chemical vapor deposition and transfer to the target substrate; Synthesize iron oleate precursor and prepare magnetic iron oxide nanoparticles with different morphologies; Surface modification of magnetic iron oxide nanoparticles using sodium citrate; The modified magnetic iron oxide nanoparticles are mixed with graphene, and the mixing time and particle size are adjusted to obtain two-dimensional flexible magnetic aggregates.
2. The method for synthesizing carbon-based flaky magnetic nanoparticle aggregates according to claim 1, characterized in that: Preparation of graphene using chemical vapor deposition, including: Using copper foil as a substrate, graphene was prepared at 1000°C and 0.5 atm by adjusting the growth rate by controlling the gas flow rate.
3. The method for synthesizing carbon-based flaky magnetic nanoparticle aggregates according to claim 1, characterized in that: The step of transferring the polymer to a target substrate comprises: transferring the polymer to a target substrate with the assistance of PMMA.
4. The method for synthesizing carbon-based flaky magnetic nanoparticle aggregates according to claim 3, characterized in that: PMMA-assisted transfer to target substrates, including: PMMA was spin-coated on the sample surface, and graphene was transferred to the target substrate by etching copper foil.
5. The method for synthesizing carbon-based flaky magnetic nanoparticle aggregates according to claim 1, characterized in that: Synthesize iron oleate precursor, including: The iron oleate precursor was prepared by dissolving ferric chloride and sodium oleate.
6. The method for synthesizing carbon-based flaky magnetic nanoparticle aggregates according to claim 5, characterized in that: Preparation of magnetic iron oxide nanoparticles with different morphologies, including: Magnetic iron oxide nanoparticles with different morphologies were prepared by thermal decomposition in oleylamine and octadecene.
7. The method for synthesizing carbon-based flaky magnetic nanoparticle aggregates according to claim 1, characterized in that: Surface modification of magnetic iron oxide nanoparticles using sodium citrate includes: The surface modification of magnetic iron oxide nanoparticles is achieved by mixing sodium citrate in an aqueous phase.
8. The method for synthesizing carbon-based flaky magnetic nanoparticle aggregates according to claim 1, characterized in that: Adjust mixing time and particle size, including: The loading amount and relative spacing of magnetic iron oxide particles on the graphene surface are adjusted to control the magnetic strength of the magnetic aggregate.
9. The method for synthesizing carbon-based flaky magnetic nanoparticle aggregates according to claim 3, characterized in that: After obtaining the two-dimensional flexible magnetic aggregate, the method further includes: The dispersibility and stability of the flexible magnetic aggregates in physiological saline were evaluated by particle surface charge analysis and hydration radius characterization.
10. A carbon-based flaky magnetic nanoparticle aggregate synthesis system, characterized in that: include: A preparation and transfer module, used for preparing graphene by chemical vapor deposition and transferring it to a target substrate; Synthesis preparation module, used to synthesize iron oleate precursor and prepare magnetic iron oxide nanoparticles with different morphologies; a modification module for surface modification of magnetic iron oxide nanoparticles using sodium citrate; The mixing preparation module is used to mix the modified magnetic iron oxide nanoparticles with graphene, and adjust the mixing time and particle size to obtain two-dimensional flexible magnetic aggregates.